A high proportion of beta-tocopherol in vitamin E is associated with poor seed longevity in rice produced under temperate conditions. Issue 4 (10th August 2019) - Lee, Jae-Sung; Kwak, Jieun; Cho, Jun-Hyeon; Chebotarov, Dmytro; Yoon, Mi-Ra; Lee, Jeom-Sig; Hamilton, N. Ruaraidh Sackville; Hay, Fiona R.
Abstract: Seeds of 15 diverse rice accessions, representing aus, indica, temperate japonica and tropical japonica subpopulations, were produced under temperate climate conditions in Korea and used for vitamin E analysis and seed storage experiments at 45°C and 10.9% seed moisture content. High γ -tocotrienol was significantly positively correlated with seed longevity. In addition, a high β -tocopherol proportion relative to δ -tocopherol was significantly negatively correlated with seed longevity. Using high-density single-nucleotide polymorphism marker data, DNA haplotype analysis showed clear allelic variations in the region of two S-adenosylmethionine synthetase genes: LOC_Os04g42095 and LOC_Os11g15410, which regulate the conversion of δ -tocopherol into β -tocopherol. Four indica accessions with rare and subpopulation-specific alleles showed a 2.3-fold lower β -/ δ -tocopherol ratio compared with accessions from other subpopulations.